Commentary: Creating a Curriculum of Intention and Justice - Fine, Michelle (LEARNing Landscapes, 2009)
In this essay we will wander into the vibrant space of a college in prison, schools and communities in which research projects have been initiated by coalitions of youth and elder activists. And we will bear witness to a lived curriculum—curriculum in the making. Shaped by the wisdom of youth and adults and the conversations between, these projects breathe a fierce intentionality to expose the contours of social injustice and a thick desire to reveal the spaces of possibility for educational engagement. At the intersection of deep inquiry, the politics of survival and affective engagement, these projects represent a way to re-vision curriculum building as a public project fed by participation, across generations, fueled by a desire for a life not yet. In each case, youth, educators and elders came together to deliberate about the purpose of the work, the depth of participation, the nature of the processes, the shape of the products we would create, and the range of worthy audiences to whom we would hold ourselves accountable.